Geomorphological environment of boulders and grain-size analysis of gravel sheets in the Southern Börzsöny, Hungary - Szeberényi, József (Hungarian Geographical Bulletin, 2010)
Previous authors draw attention to gravel sheets in the south of Börzsöny Mountains, which are not related to Pleistocene gravels of Danube terraces. Two areas were studied: in the south-western and south-eastern parts of the mountains. These pebbles have survived in good condition. Although there are considerable horizontal distance and difference in altitudes between the two gravel sheet locations, the geomorphological and grain-size analyses have resulted in some important conclusions. The geomorphology of the two areas is very similar to each other. The correlational statistical analysis of grain size shows similarity between the samples collected from the occurrences. In the environment of both locations some boulders are found composed of quartzite. They are usually between 20 and 40 cm in diameter, but some of them are of 60 cm size. In the opinion of the author these boulders were very probably transported by fl oating frozen in ice floes.